PDD-NOS: the "unknown continent" - Towbin, Kenneth (Henry Stewart Talks, 2010)
PDD-NOS (Pervasive Developmental Disorder Not Otherwise Specified) as a diagnosis concept, Qualitative impairment in social interaction and communication, Restricted, repetitive and stereotyped patterns of behavior, interests and activities, History, Epidemiology, Current and illegitimate clinical use, Difficult diagnosis, Evidence for a continuum, Genetic risk, Adult outcome of PDD-NOS, Adult outcome of ASDs, Outcome from 2-9 years of age, Differential diagnostic considerations, Features of semantic pragmatic disorder, PDD-NOS and the 'broad phenotype', Definition of BAP, Treatment and PDD-NOS, Clinical practice and PDD-NOS, Considerations for the future